Quantification of the effects of robotic-assisted gait training on upper and lower body strategy during gait in diplegic children with Cerebral Palsy using summary parameters. Issue 2 (3rd February 2022) - Piccinini, Luigi; Cimolin, Veronica; Storm, Fabio; Di Girolamo, Gabriella; Biffi, Emilia; Galli, Manuela; Condoluci, Claudia
Abstract: The effects of robotic-assisted gait training on upper and lower body strategy during gait in diplegic children with Cerebral Palsy (CP) were quantified using summary parameters (Upper Body Profile Score (UBPS) and Gait Profile Score (GPS)). Firstly, the upper body strategy during gait was assessed in 73 children with CP and 15 healthy children (Control Group: CG): patients with CP exhibited higher values of most of the summary parameters of the upper body position than the CG. Then, the effects of a robotic-assisted gait training in a sub-group of 35 children by means of UBPS were evaluated. After robotic-assisted gait training program, no significant differences as for the summary parameters (UBPS and GPS). However, considering the specific variables scores, significant improvements are displayed as for the upper body parameter on the sagittal plane (Upper Body Ant/Pst index) and the lower limbs, in particular pelvis (Pelvic Ant/Pst and Pelvic Int/Ext indices) and as for walking velocity. A sort of reorganization of full-body kinematics, especially at upper body and proximal level (pelvis) seems to appear, with a new gait approach, characterised by a better strategy of the upper body associated with a significant improvement of the pelvis movement.